CVD-assisted fabrication of hierarchical microparticulate Li2TiSiO5-carbon nanospheres for ultrafast lithium storage. Issue 26 (26th June 2020) - Kong, Dejia; Shen, Li; Mo, Runwei; Liu, Jiaxu; Tao, Ran; Shi, Wenyue; Ma, Shengxiang; Zhang, Chen; Lu, Yunfeng
Abstract : Introducing a high-quality carbonaceous coating on microparticulate Li2 TiSiO5 (LTSO) by chemical vapor deposition (CVD) yields a practical composite anode (LTSO/C) with graphite-like capacity and Li4 Ti5 O12 -like rate capability. Abstract : Particular recent interest has been given to the Li2 TiSiO5 (LTSO) anode material owing to its low lithiation potential (0.28 V vs. Li/Li + ) and decent theoretical capacity (308 mA h g −1 ). However, its poor electronic conductivity (∼10 −7 S m −1 ) fundamentally limits the utilization of this material, and current strategies fail to tackle such issues in practical ways. Herein, a hierarchical microparticulate LTSO-carbon composite (LTSO/C) is fabricated by chemical vapor deposition (CVD), where microsized LTSO/C particles assembled from nanospheres guarantee a practical tap density of ∼1.3 g mL −1 . Meanwhile, significantly elevated conductivity of LTSO/C (∼10 3 S m −1 ) is achieved by a thin layer (15 nm) of graphitic carbon growth on LTSO, which is theoretically catalyzed by the surface functional groups on the parent LTSO. The electrochemical characterization of LTSO/C reveals a superior graphite-like volumetric capacity of 441.1 mA h cm −3 and Li4 Ti5 O12 -like rate capability (120.1 mA h cm −3 at 4.5 A g −1 ), providing inspiring guidance for designing analogous Ti or Si-based compounds for ultrafast lithium storage materials.